The Re-Integration of Iran into the Global Energy Markets and its Geopolitcal Implications - N. E. Semenov (Сравнительная политика)
Recent negotiations earlier this year in Switzerland brought hope to the generation of Iranians whose life have been altered by the damaging influence of international sanctions on the country’s economy. Recent high-level negotiations in Vienna have a tangible promise of final relief for ordinary people. This nuclear deal has a high potential to influence on global energy markets, since Iran could be a major oil and natural gas supplier to the European Union and a number of Asian countries, since it holds fourth largest reserves of oil and largest reserves of natural gas. Decades of economic isolation from western technologies have had a detrimental effect on the industrial development and the economy needs major investments in order to bring Iranian gas and oil flowing in Eurasia. Iran has some idle capacity of oil waiting to pave its way to the customer once the sanctions are effectively lifted after the accord struck in Vienna on June, 14, and this certainly puts additional pressure on oil and gas prices. Moreover, Iran’s economic growth can restore its political influence in the Middle East which has already been source of contention in Israel and some Arabian countries.